PALAEOMAGNETISM OF THE BAYAN GOL FORMATION, WESTERN MONGOLIA - Evans D.A.; Kirschvink J.L.; Zhuravlev A.Yu.; Budney C.J. (My University, 1996)
Oriented samples of the Lower Cambrian Bayan Gol Formation from Salaany Gol, Mongolia, were collected at roughly 5 m stratigraphic intervals for palaeomagnetic analysis. Progressive alternatingfield and thermal demagnetization isolated two magnetic components: a present-field overprint, typically removed by 10 mT fields and ~200°C heating; and a high-coercivity, high-unblocking-temperature (550–600 °C), predominantly single-polarity component that was imparted to the rocks prior to early or middle Palaeozoic deformation. Single-polarity magnetization at Salaany Gol contrasts with results from Lower Cambrian rocks on the Siberian platform, previously considered correlative with the Bayan Gol Formation, which show a prominent change in polarity bias near the top of the Tommotian Stage. Two hypotheses can explain this discrepancy. First, the entire Bayan Gol Formation may correlate with the predominantly reversely polarized, lower half of the Tommotian Stage in Siberia. This model is consistent with plausible interpretations of δ13C profiles for the Zavkhan basin and the Siberian platform. Alternatively, the characteristic magnetic direction from our samples may be a pre-fold overprint. If post-accretionary, then comparison with Siberian palaeomagnetic results suggest a Silurian–Devonian remagnetization age, and existing bioand chemostratigraphic correlations provide the most reliable spatial and temporal links between the Zavkhan basin and the Siberian platform. If the observed magnetic directions are primary or an immediate overprint then they may be used to constrain the early Cambrian palaeogeography of the Zavkhan basin and the Palaeo-Pacific Ocean. Mean inclination of 62 ±4° corresponds to a palaeolatitude of 44 ±5°, several thousand kilometres from the equatorial Siberian craton
Keywords: Cambrian; Palaeozoic; Devonian; Silurian; Paleozoic::Silurian; Палеозой; Paleozoic::Devonian; Палеозой::Девонская; Палеозой::Кембрийская; Палеозой::Силурийская; Paleozoic::Cambrian; Paleozoic